2022
DOI: 10.3390/molecules27092686
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Degradation Reaction of Hydroxide Ions with Several Quaternary Ammonium Head Groups of Anion Exchange Membranes Investigated by the DFT Method

Abstract: Commercialization of anion exchange membrane fuel cells (AEMFCs) has been limited due to the chemical degradation of various quaternary ammonium (QA) head groups, which affects the transportation of hydroxide (OH−) ions in AEMs. Understanding how various QA head groups bind and interact with hydroxide ions at the molecular level is of fundamental importance to developing high-performance AEMs. In this work, the binding and degradation reaction of hydroxide ions with several QA head groups—(a) pyridinium, (b) 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…The computed energies are low compared to other studies, 47 51 sign of lower chemical stability of the monomer. However, it should be noted that the implicit solvation model significantly underestimates the obtained values which would be higher, considering explicit water molecules.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…The computed energies are low compared to other studies, 47 51 sign of lower chemical stability of the monomer. However, it should be noted that the implicit solvation model significantly underestimates the obtained values which would be higher, considering explicit water molecules.…”
Section: Resultscontrasting
confidence: 74%
“…The TMA functional groups are subjected to different degradation mechanisms at high temperatures and alkaline environments, mainly to nucleophilic substitution (S N 2), Ylide formation, and Hofmann elimination. ,, The degradation process is closely related to the level of hydration. Therefore, the interaction of the TMA head group with OH – and different hydration levels will be analyzed with structures 4, 7, and 8, with λ equal to 0, 2, and 4 respectively, simulating the hydrated condition by explicitly adding water molecules to the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ab initio calculations, the ground state for a set of atoms is obtained by solving the Schrodinger equation. The time-independent Schrodinger equation for the collection of many atoms is the basis of quantum mechanics (QM) [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Most of the computational studies on the chemical stability of AEM study via DFT calculations.…”
Section: Electronic Structure Calculations Based On the Density Funct...mentioning
confidence: 99%
“…More recently, Karibayev et al studied the chemical stability and transportation of ion trends, for the various QA head groups using quantum chemical properties, such as binding energies, LUMO energies, nucleophilic substitution reaction, and activation energies [ 94 ]. The results suggested that the trimethylhexylammonium-based QA head group is the most stable QA head group, while the pyridinium-based QA head group is the least stable QA head group.…”
Section: Electronic Structure Calculations Based On the Density Funct...mentioning
confidence: 99%